1999
DOI: 10.1038/sj.onc.1202801
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of TACC1, an embryonically expressed, potentially transforming coiled coil containing gene, from the 8p11 breast cancer amplicon

Abstract: Ampli®cation of several chromosomal regions have been observed in human breast carcinomas. One such region, 8p11, is ampli®ed in 10 ± 15% of tumor samples. Although the FGFR1 gene is located close to this region, and is often included within the amplicon, the observation that tumors exhibiting 8p11 ampli®cation do not always overexpress FGFR1 suggests that another gene located close to FGFR1 is involved in the tumorigenic process. We now report the precise location of four expressed sequence tags (ESTs) within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
147
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 111 publications
(150 citation statements)
references
References 14 publications
2
147
1
Order By: Relevance
“…In mammals, TACC1 appears to be more widely‐expressed than TACC3, with TACC1 showing almost ubiquitous expression in adult murine and human tissues [Sadek et al, 2003; Still et al, 1999]. However, TACC1 is also spatiotemporally regulated during murine development [Lauffart et al, 2006; Still et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, TACC1 appears to be more widely‐expressed than TACC3, with TACC1 showing almost ubiquitous expression in adult murine and human tissues [Sadek et al, 2003; Still et al, 1999]. However, TACC1 is also spatiotemporally regulated during murine development [Lauffart et al, 2006; Still et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, TACC1 appears to be more widely‐expressed than TACC3, with TACC1 showing almost ubiquitous expression in adult murine and human tissues [Sadek et al, 2003; Still et al, 1999]. However, TACC1 is also spatiotemporally regulated during murine development [Lauffart et al, 2006; Still et al, 1999]. Further characterization of the human TACC family proteins by immunostaining demonstrated that all three family members interact with MTs and specifically concentrate at centrosomes and mitotic spindles [Gergely et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that Tacc1 mRNA expression is maximal prior to Day 11 of mouse embryonic development, with expression later in development decreasing radically until lower levels are maintained in most adult tissues (Still et al, 1999a). However, to date the developmental expression of the Tacc1 protein in the mouse has not been defined.…”
Section: Tacc1 Protein Expression During Mouse Embryogenesismentioning
confidence: 97%
“…Functional homologues of these proteins are present in organisms from yeast to man and there is growing evidence that supports a conserved role for the TACCs in the processes underlying the normal development of these organisms (Gergely et al, 2000b;Piekorz et al, 2002;Srayko et al, 2003;Le Bot et al, 2003;Boulton et al, 2004). Initial analysis has suggested that Tacc1 and Tacc3 mRNA levels are expressed at high levels during embryogenesis and are then downregulated as differentiation proceeds, finally being expressed either at low levels or only in restricted tissues (Still et al, 1999a;Sadek et al, 2000). By contrast, Tacc2 is expressed throughout development and this expression persists in the majority of adult tissues (Lauffart et al, 2003;Schuendeln et al, 2004), although changes in the distribution of splice variants may occur in tissue progenitor cells (Still et al, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation